P‐258: Late‐News Poster: New Approach for Achieving Perfect Black of WOLED - Kim, Minhyung; Roh, Sudong; Lim, Chungsun; Lee, Taerim; Bae, Sungjoon; Shin, Woosup; Lee, Hyeonwoo (SID International Symposium Digest of technical papers, 2024)
OLED displays have excellent black characteristics as a self‐emitting device, but in the bottom emission structure, reflections from external light are generated by the use of highly reflective metal electrodes. In order to control this, an appropriate anti‐reflective function for each wavelength has been given to the film to realize Neutral Black. In this paper, we would like to propose a new method to realize more neutral black and high clarity CR by adjusting the QWP and surface treatment of the pol layer and panel technology that affect the reflective properties.